REVIEW BUKU MENJERAT GUS DUR - Nilma Yola (Hadharah: Jurnal Keislaman dan Peradaban, 2021)
This paper discusses the review of a book written by Virdika Rizky Utama with the title Menjerat Gus Dur. The method used in this paper is library research. The purpose of writing this book is to find a light on the impeachment of President Gus DUR. The result of the research is the intervention of Amin Rais and other political opponents of Gus Dur in trapping Gus Dur to be impeached. Conclusion: in a political world that is honest and does not want to be cheated on, then A will be removed.